Propuesta de un modelo didáctico de indagación para favorecer la actitud científica, a través de entornos virtuales, de los estudiantes que migran al primer grado del nivel secundario, en el área de Ciencia, Tecnología y Ambiente - Moya Rodriguez, Hunter Humer (2019)
The present research, of a descriptive - explanatory nature, sought, through the theoretical reflection, to propose a didactic model, whose dynamic element was the investigation, to favor the scientific attitude in students who migrate to the first grade of secondary level and whose procedures of performance will be vehicled through virtual environments._x000D_ The theoretical proposal has as an independent variable, for a further application, the Scientific Attitude Model towards the CTA area (EACTA). The model is presented in its main vectors, with the emphasis placed on inquiry._x000D_ Inferences are made about the phylogenetic characteristics of the human being and that are more evident in children, as well as the explanations that are made to make credible the relationship that these characteristics would have, in their theoretical correlation, with the presented proposal._x000D_ The proposal has a strong theoretical basis in the suggestions of the model Eggen, Piaget and Bruner, theoreticians, all of them, who emphasize much the activity and the sense of curiosity of the child. This sense of curiosity, taking away some negative connotations, is the basis of the inquiry that is the central element that structures the proposal._x000D_ Finally, it is proposed, as a real possibility, that the Scientific Attitude Model towards the CTA area (EACTA), because its foundations are relevant and plausible to apply, improve - in a later application, through virtual environments - the provision towards science.